Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1112/s0010437x07002941
|View full text |Cite
|
Sign up to set email alerts
|

Invariants of Newton non-degenerate surface singularities

Abstract: We recover the Newton diagram (modulo a natural ambiguity) from the link for any surface hypersurface singularity with nondegenerate Newton principal part whose link is a rational homology sphere. As a corollary, we show that the link determines the embedded topological type, the Milnor fibration, and the multiplicity of such a germ. This proves (even a stronger version of) Zariski's Conjecture about the multiplicity for such a singularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Therefore, even for hypersurface singularities the two values eu(H * ) and min γ eu(H 0 (γ)) might be different. Here we wish to recall that in [9] it is shown that for such germs from M one can recover the Newton diagram of the equation, hence the equisingularity type of the germ too. Hence, in principle, p g can be recovered from M ; however this statement does not indicate any topological candidate for p g .…”
Section: Some Conjectures Results and Examplesmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, even for hypersurface singularities the two values eu(H * ) and min γ eu(H 0 (γ)) might be different. Here we wish to recall that in [9] it is shown that for such germs from M one can recover the Newton diagram of the equation, hence the equisingularity type of the germ too. Hence, in principle, p g can be recovered from M ; however this statement does not indicate any topological candidate for p g .…”
Section: Some Conjectures Results and Examplesmentioning
confidence: 97%
“…If a ∈ A corresponds to △ ∈ F \ F c then N a = N △ . All the other vectors are determined in a unique way by the next identities (see [9]):…”
Section: (The Algorithm)mentioning
confidence: 99%
“…According to this, for such a germ one defines the Newton polytope N using the nontrivial monomials of the defining equation of the germ, and one proves that several invariants of the germ can be recovered from N ; see eg Braun and Némethi [10]. For example, by a result of Merle and Teissier [30], the geometric genus p g equals the number of lattice points in ..Z >0 / 3 \ N /.…”
Section: A 'Classical' Connection Between Polytopes and Gauge Invariamentioning
confidence: 96%
“…The purely combinatorial nature of the description we make of the manifold ∂F opens the way for the computation of a great number of examples through a future implementation in a computer program. But it also calls for more theoretic work, such as for example extending what is done in [BN07], where Braun & Némethi do the opposite work, retrieving a possible Newton polyhedron of a function f : C 3 → C having a given graph manifold as boundary of its Milnor fiber, under the hypothesis that this manifold is a rational homology sphere. Another use of this method would be to answer the widely open question of which manifolds can appear as boundaries of Milnor fibers of non degenerate surface singularities.…”
Section: Introductionmentioning
confidence: 99%